An investigation into mental health care deficits in South Africa: exploring an alternative intervention strategy - Daniels, Ingrid (Department of Social Development, 2019)
This study investigates mental health care deficits in South Africa and explores an alternative intervention strategy that promotes an integrated community-based intervention model to reach the vulnerable majority living with the debilitating consequences of mental illness. The research is grounded in human rights, empowerment and human scale development theories. A mixed-methods research design consisting of a dominant quantitative methodology complemented by a qualitative methodology was adopted. The research design was carried out in three sequential phases. The first phase of the study involved an online survey with 19 mental health professionals employed at State psychiatric facilities and 90 social workers at 17 mental health non-government organisations. The second phase involved 5 focus group discussions with a total of 40 mental health service users from the Western Cape, Eastern Cape, KwaZulu-Natal, Northern Cape and Limpopo Provinces. The third and final phase of the study involved telephonic interviews with two key informants, using a semi-structured interview guide. Purposive sampling procedures were used to recruit respondents from all nine provinces in South Africa. Findings indicate that less than half of the mental health professionals (49%, n=53) reported that the National Mental Health Policy Framework and Strategic Plan 2013‒2020 is a very good policy, whereas 42.6% (n=46) agreed that the policy is highly appropriate for a developing country. The Chi-square test showed a significant relationship between respondents’ perceptions of a good policy and its appropriateness for mental health care in South Africa [χ² (9, n=109) = 120.5, p <.000]. The focus group findings indicated that only a few service users were aware of the policy as a 'strategic plan’ whilst the majority of focus group participants were unfamiliar with the policy and thought that it should be summarised in clear language and disseminated. The issue of stigma experienced and confirmed by service users was regarded as a major barrier to mental health care – the majority (89.9%, n=98) of respondents indicated that mental illness remains one of the most highly stigmatised conditions in South Africa. There is a significant relationship between how well mental illness is understood and the stigma associated with mental illness [χ² (16, n=109) = 40.7, p<.001]. The Chi-square test indicated a significant association between mental health professionals’ perception about vulnerability and the discrimination against mental health service users [χ² (9, n=109) = 25.0, p<.003]. These findings were confirmed by the focus group participants who said: “As long as there is stigma – we as mental health patients get judged by our community, by our families and people around you – then nothing will change”. The majority (94.5%, n=103) of respondents agreed that people with mental illness are more vulnerable to abuse by society than those without mental illness. The majority (80.7%, n=88) of mental health professionals reported that the medical model is the dominant approach to diagnosis and treatment of mental illness in South Africa. The focus group participants were keenly aware that “just taking your medication isn’t always balancing out”. The majority of mental health professionals (83.5%, n=91) agreed that poor socio-economic conditions increased mental illness, whereas 73.4% (n=80) agreed that there was a direct link between poverty and the increase in demand for mental health services. The Chi-square test indicated that there is a significant association between poor socio-economic conditions and the increased demand for mental health services in South Africa [χ² (16, n=109) = 199.2, p<.001]. Focus group discussions confirmed this link between poverty and mental illness with participants highlighting the constraints of meagre grants and their inability to find jobs. Findings from the key informants concur with the aforementioned main findings. Conclusions drawn from the triangulated findings show the major deficits in treatment; the lack of resources and funding; the lack of community-based mental health interventions and the exclusion of mental health service users as significant role-players. Finally this study both recommended and designed a comprehensive patient-centred, integrated community-based mental health service model that is aligned with South Africa’s National Mental Health Policy. The proposed model took into account the perspectives of mental health professionals, mental health service users, and findings from the survey respondents, as well as ideas from 'best practice models’ found in Zimbabwe, Uganda, Brazil and India – and was corroborated by key informants.